2014
DOI: 10.1371/journal.pone.0089954
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Polymorphism of the Endogenous Opioid Dynorphin Modulates Monetary Reward Anticipation in the Corticostriatal Loop

Abstract: The dynorphin/κ-opioid receptor (KOP-R) system has been shown to play a role in different types of behavior regulation, including reward-related behavior and drug craving. It has been shown that alleles with 3 or 4 repeats (HH genotype) of the variable nucleotide tandem repeat (68-bp VNTR) functional polymorphism of the prodynorphin (PDYN) gene are associated with higher levels of dynorphin peptides than alleles with 1 or 2 repeats (LL genotype). We used fMRI on N = 71 prescreened healthy participants to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…In addition, it activated the inferior frontal gyrus (IFG), inferior parietal lobe (IPL), and precuneus. The behavioral data demonstrated that participants were faster in reaction time to monetary cues comparing to non-monetary ones, which is in line with other studies which used similar task 20 21 . Before we interpret these findings in more detail, we will discuss the main effects and interaction results of our design.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it activated the inferior frontal gyrus (IFG), inferior parietal lobe (IPL), and precuneus. The behavioral data demonstrated that participants were faster in reaction time to monetary cues comparing to non-monetary ones, which is in line with other studies which used similar task 20 21 . Before we interpret these findings in more detail, we will discuss the main effects and interaction results of our design.…”
Section: Discussionsupporting
confidence: 91%
“…However, when they applied damage to the fibers passing near or through the OFC, it caused an impairment of behavioral flexibility (Rudebeck et al, 2013 ). This is in line with our previous PDYN study (Votinov et al, 2014 ) which had also demonstrated a difference between genotype groups in functional connectivity between OFC and other regions.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, similar to the effect on the striatum, KOR agonists also affect prefrontal cortex by decreasing dopamine overflow (Margolis et al, 2006 ; Tejeda et al, 2012 ). Our previous dynorphins study (Votinov et al, 2014 ) also demonstrated differences in the brain activation for medial orbitofrontal cortex between HH and LL genotype groups. In that study we observed that HH group had higher activation in mOFC than the LL group in response to upcoming monetary reward, which interpreted as increased reward sensitivity in the HH group.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The underlying mechanism for clinical efficacy of opioid antagonists in alcoholism is generally described as blocking the increased MOR and β -endorphin stimulation of MOR in mesolimbic dopaminergic pathway thus reducing activity and the rewarding effects of alcohol and craving ( Johnson and North, 1992 ). Given our observation that MOR availability is unchanged in PG, the mechanism of action for opioid antagonists may therefore involve other opioid receptors such as kappa ( Votinov et al , 2014 ) or processes other than those involved in pleasure and reward, such as impulsivity.…”
Section: Discussionmentioning
confidence: 99%